Zakat, Islamic Corporate Social Responsibility And The Implementation Of Sharia Good Governance On The Reputation Of Sharia Commercial Banks - Riyanto Setiawan Suharsono; Ibna Kamelia Fiel Afroh; Gardina Aulin Nuha; Muhammad Firman Febriansyah (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study examines the influence of Zakat, Islamic Corporate Social Responsibility (ICSR), and Sharia Good Governance (GGBS) on the reputation of Sharia Commercial Banks in Indonesia. Reputation plays a central role in shaping public trust and strengthening the institutional credibility of Islamic financial institutions, particularly as the industry continues to expand in alignment with national and global Islamic finance agendas. Using a quantitative approach, this research analysed secondary data obtained from annual reports of Islamic commercial banks registered with the Financial Services Authority (OJK) for the 2019–2023 period. Multiple linear regression was employed to measure both the individual and simultaneous effects of the three independent variables on bank reputation. The findings reveal that zakat exerts a significant positive effect on reputation, demonstrating its strategic role as both a religious obligation and an instrument of socio-economic empowerment. Zakat distribution functions as a credible signal that reinforces stakeholder trust and enhances institutional legitimacy. Conversely, ICSR does not show a significant effect on reputation, indicating that current CSR disclosures may not yet be perceived as strong value drivers by the public or may lack strategic visibility. Meanwhile, Sharia Good Governance (GGBS) demonstrates a significant positive influence, affirming the importance of transparency, accountability, compliance, and ethical governance in shaping the reputation of Islamic banks. Overall, the study highlights the need for Islamic banks to strengthen governance mechanisms and optimise zakat management to reinforce public confidence. It also suggests that ICSR practices require greater strategic alignment and communication to meaningfully contribute to institutional reputation.